Industrial policy and subsoil use: an integration of science, education and industry - Yu. B. Vinslav; S. V. Lisov (Известия высших учебных заведений: Геология и разведка, 2015)
The reasons of actualization of processes of the integration of science, education, industry in economics are considered. The post-reform economical situation didn’t help the development of the persistent long-term integration of industrial, scientific and educational organizations. The main factors, hampering this integration, are systemized. The experience of the integration of the industrial, scientific, educational structures in the subsoil use sector. The principals of the organization of integrated activity are worked out, which concern: actualization of the needs of the industry in innovations and competitive staff; accounting of the factor of «fall down» of the market in state regulation; the balanced industrial, scientific-technical and educational policy at macro- and meso-levels; the presence of leading organization in the interaction; project approach to the interaction activity. The organizational-management algorithm of creation of educational-scientific-industrial cluster is recommended.